Proximity to School and Physical Activity Among Middle School Girls: The Trial of Activity for Adolescent Girls Study - Cohen, Deborah A. (2006)
BACKGROUND: Proximity to routine destinations is an important correlate of physical activity. We examined the association between distance from school and physical activity in adolescent girls. METHODS: We mapped the addresses of 1554 sixth-grade girls who participated in the Trial of Activity for Adolescent Girls (TAAG) Study and calculated the shortest distance from home to school along the street network. Using a hierarchical design we examined the association between MET-weighted moderate to vigorous physical activity (MW- MVPA) and distance to school, while controlling for potential confounders. RESULTS: Distance to school was inversely associated with weekday MW- MVPA for middle school girls. For every mile the girls lived from their schools, they engaged in an average of 13 fewer MET- weighted minutes per week. CONCLUSIONS: Distance to school is inversely associated with MW-MVPA. The most adversely affected girls lived more than 5 miles from school. Time spent commuting could explain reduced time for physical activity.